A elocução do amor em Tibulo - Martins, Maria Helena Aguiar (2016)
This dissertation investigates the elocution of eleven poems from Albius Tibullus (c. 55-19 BC) work: poems 1.1-6, 1.8-9, 2.3-4 and 2.6. The demilitation of this corpus of analysis is based on the erotic subject and it is also based on the characters to which the poems are addressed: Delia, Marathus and Nemesis; the formal investigation of the elocution sustains the discussion about some aspects from this subject; therefore, we divided the poems analyzed in three cycles; the elocution of those cycles is going to be analyzed separately and compared to each other. In order to develop this research, as theoretical foundation we use research and commentaries on the work of Tibullus, rhetorical texts from Greco-Roman Antiquity, and researches about rhetoric, especially those woks that develop the elocution. The analysis is based mainly on Ad Herennium and also on Manual de Retórica Literária, from Lausberg. A further discussion of Latin poetry requires an examination of the elocution, since the Latin poets had rhetoric as their foundation. It is noticeable, that Tibullus selection and arrangement of the words in his verses utilizes figures of speech in order to mimic their content; moreover the disposition rise up the erotic content of the poems.